GEOPROCESSAMENTO COMO FERRAMENTA NO LICENCIAMENTO AMBIENTAL DE POSTOS DE COMBUSTÍVEIS / Geoprocessing as a tool in the environment licence of peddling fuel ranks - Paulo Tarso Sanches de Oliveira; Fabio Martins Ayres; Getúlio Ezequiel da Costa Peixoto Filho; Ivan Pedro Martins; Nicia Maria Machado (Sociedade & Natureza)
The City Department of Environment and Sustainable Development (SEMADES, acronym in portuguese)has paid special attention to the monitoring of the environmental quality, mainly in the monitoring ofactivities that have high polluting potential. So, this work aims to avaluate the application of geotechnologies as a tool in the taking of decisions at the management and environmental monitoringof gas stations located at the Municipal District of Campo Grande - MS. For such, a spatialization ofthe gas station was made and the environmetal conditions of each gas station were surveyed, Alsocrossings with the hydrography, Areas of Permanent Preservation (APP) and the Geotechnical letter ofthe Municipal District have been carried through. The results had demonstrated that the usedgeoprocessing techniques will be able to assist the SEMADES at the control, monitoring and taking ofdecision in the Environmental licensing of gas stations, this can also be applied to other licensedactivities.